The impact of atypical antipsychotics on the development of type 2 diabetes mellitus - Sabina E. Kurtmambetova; Yana V. Andrukh; Ruslan E. Kurtmambetov; Elena N. Primysheva; Irina N. Repinskaya (LLC "MEDIAFORMAT", 2024)
Atypical antipsychotics (novell atypical generation antipsychotics) have entered clinical practice recently, but despite this, they have already managed to occupy one of the leading positions in modern therapy of mental disorders such as schizophrenia and bipolar affective disorder. It is known that treatment with antipsychotics of both generations is associated with a number of side effects. When using atypical antipsychotics, metabolic disorders, including carbohydrate metabolism, occupy a leading place. A number of scientific studies, the analysis of which we are conducting in this review, describe the mechanisms of development of such changes in glucose homeostasis as hyperglycemia and insulin resistance in patients receiving therapy with second-generation antipsychotics (atypical). Another proven side effect is an increase in appetite and an increase in body weight. It is obvious that such metabolic changes have the potential to lead to the development of type 2 diabetes mellitus in the long term. The relevance of the study lies in the fact that the use of atypical antipsychotics is not always among the causes of drug-induced diabetes mellitus. In this regard, not all internists, endocrinologists, general practitioners, and sometimes even psychiatrists consider patients receiving treatment with these drugs to be at increased risk. Consequently, primary and secondary prevention of diabetes mellitus among such patients may not be carried out or may be insufficient. In this review, through meta-analysis, we summarized data on the effect of the main representatives of atypical antipsychotics on the possibility of developing type 2 diabetes mellitus, and also examined in more depth the pathogenesis of carbohydrate metabolism disorders in patients receiving therapy with these drugs.